Teaching Framework of Stunting for Vocational Midwifery Students: A Document Review - Martha Debora Korompis; Frederika Nancy Losu (Universitas Aisyah Pringsewu, 2023)
The teaching of stunting for vocational midwifery education students is not yet standardized. Even though midwife graduates bear a big responsibility in participating in stunting prevention programs both at the local and national levels. This inequality can result in the unpreparedness of graduates of midwifery education in dealing with the problem of stunting. This research aims to develop a clear stunting teaching framework related to the distribution of cognitive and psychomotor content for midwifery vocational students. This study used the document review method. Data were collected from reputable journals for the last five years from Google Scholar, PubMed, Researchgate, and Semantic Scholar. Other official documents were filtered from Google Engine. Data processing used PRISMA analysis by applying 3 steps, namely, identification, screening for eligibility, and included. Inclusion criteria: stunting, midwifery students, and teaching cognitive and psychomotor domains, in English or Indonesian. The exclusion criteria were education other than midwives, and domains other than cognitive and psychomotor, documents other than English or Indonesian. Data analysis using PICOT to determine Population, Problem, Intervention, Comparison, Outcome, and Time. The results of the PICOT selection show that the teaching framework for stunting material includes 40% of the theory in class which contains: stunting theory, national health system, anthropometrics, health promotion, and communication and presentation skills. While teaching skills 60% include health assessment practices, communication and presentation skills, and anthropometric measurements. The psychomotor domain is carried out in the laboratory and field practice. The stunting teaching framework is outlined in local content materials in areas with high stunting prevalence rates. This study recommends that the stunting teaching module gives a clear emphasis on the cognitive domain of 40% and 60% psychomotor. Abstrak: Pengajaran stunting bagai mahasiswa pendidikan kebidanan vokasi belum berstandard. Padahal lulusan bidan memanggul tanggungjawab besar dalam keikutsertaan program penanggulangan stunting baik tingkat lokal maupun nasional. Ketimpangan ini bisa mengakibatkan ketidaksiapan lulusan pendidikan bidan dalam menghadapi masalah stunting. Tujun penelitian ini untuk mengembangkan kerangka pengajaran stunting yang jelas terkait pembagian muatan kognitive dan psikomotor bagi mahasiswa vokasi kebidanan. Penelitian ini menggunakan metode document review. Data dikumpulan dari jurnal bereputasi selama lima tahun terakhir dari Google Scholar, PubMed, Researchgate, and Semantic Scholar. Dokumen resmi lainnya disaring dari Google Engine. Olah data menggunakan PRISMA analysis dengan menerapkan 3 langkah, yaitu identifikasi, screening for eligibility dan Included. Kriteria Inklusinya: stunting, midwifery students, and teaching domain cognitive and psychomotor, dalam Bahasa Inggris atau Indonesian. Kriteria Eksklusinya pendidikan selain midwife, dan domain selain cognitive and psychomotor, dokumen selain bahasa Inggris atau Indonesian. Analisis data dengan menggunakan PICOT guna menentukan Populasi, Problem, Intervensi, Komparasi, Luaran, dan Waktu. Hasil PICOT selection menunjukkan kerangka pengajaran materi stunting mencakup 40% teori di kelas yang berisi: teori stunting, system kesehatan nasional, antropometric, promosi kesehatan, dan communication and presentation skills. Sedangkan pengajaran keterampilan 60% meliputi praktik pengkajian kesehatan, communication and presentation skills, dan pengukuran antropometric. Domain psikomotor dilakukan di laboratorium dan praktik lapangan. Kerangka pengajaran stunting dituangkan dalam materi muatan lokal di wilayah dengan angka prevalensi stunting tinggi. Penelitian ini merekomendasikan modul pengajaran stunting memberikan penekanan yang jelas pada domain kognitif 40% dan psikomotor 60%.